Effects of road construction noise on golden‐cheeked warblers: An update. (19th June 2017) - Long, Ashley M.; Colón, Melanie R.; Bosman, Jessica L.; Mcfarland, Tiffany M.; Locatelli, Anthony J.; Stewart, Laura R.; Mathewson, Heather A.; Newnam, John C.; Morrison, Michael L.
ABSTRACT: Previously, we reported results from an impact assessment that examined the effects of road construction noise on habitat selection and productivity of an endangered songbird, the golden‐cheeked warbler ( Setophaga chrysoparia ; warbler hereafter), in rural Texas, USA. We found no evidence that road construction or traffic noise negatively influenced warbler territory density, territory placement, pairing success, or fledging success during 3 years of road construction activities (2007–2009). In addition, warblers exhibited few acute responses to construction noise played at close range (2008–2009). Herein, we expanded on previous results to include an additional year of construction data (2010) and 3 years of post‐construction data (2011–2013) because birds may exhibit delayed responses to disturbance. We also examined the potential influence of road construction noise and activity on warbler song characteristics because birds may sing at higher minimum frequencies if loud noise masks their communication signals. Similar to previous findings, we found no evidence that road construction or traffic noise negatively influenced warblers in our rural study area. However, noise levels varied little across experimental and control study sites, with increasing distance from the road, or between the construction and post‐construction phases of our study. Warblers may respond negatively to louder noise or other disturbances that accompany construction activities (e.g., vibrations), but our comparisons across study sites, the results of our playback experiment, and data collected during concurrent studies in urban Texas and on military land suggest this is unlikely. © 2017 The Wildlife Society. Abstract : Previously, we found no evidence that road construction or traffic noise negatively influenced golden‐cheeked warbler ( Setophaga chrysoparia ) territory density, territory placement, pairing success, or fledging success during 3 years of road construction activities in rural Texas, USA. We extended our previous work to include an additional year of construction data and 3 years of post‐construction data and found no evidence of lag effects in golden‐cheeked warbler responses to road construction or traffic noise at our study sites.